MiR155-5p Inhibits Cell Migration and Oxidative Stress in Vascular Smooth Muscle Cells of Spontaneously Hypertensive Rats - Nan Wu; Chao Ye; Fen Zheng; Guo-Wei Wan; Lu-Lu Wu; Qi Chen; Yue-Hua Li; Yu-Ming Kang; Guo-Qing Zhu (MDPI AG, 2020)
Migration of vascular smooth muscle cells (VSMCs) is essential for vascular reconstruction in hypertension and several vascular diseases. Our recent study showed that extracellular vesicles derived from vascular adventitial fibroblasts of normal rats inhibited VSMC proliferation by delivering miR155-5p to VSMCs. It is unknown whether miR155-5p inhibits cell migration and oxidative stress in VSMCs of spontaneously hypertensive rats (SHR) and in angiotensin II (Ang II)-treated VSMCs. The purpose of this study was to determine the role of miR155-5p in VSMC migration and its underlying mechanisms. Primary VSMCs were isolated from the aortic media of Wistar-Kyoto rats (WKY) and SHR. Wound healing assay and Boyden chamber assay were used to evaluate VSMC migration. A miR155-5p mimic inhibited, and a miR155-5p inhibitor promoted the migration of VSMC of SHR but had no significant effect on the migration of VSMC of WKY. The miR155-5p mimic inhibited angiotensin-converting enzyme (ACE) mRNA and protein expression in VSMCs. It also reduced superoxide anion production, NAD(P)H oxidase (NOX) activity, as well as NOX2, interleukin-1β (IL-1β), and tumor necrosis factor α (TNF-α) expression levels in VSMCs of SHR but not in VSMCs of WKY rats. Overexpression of miR155-5p inhibited VSMC migration and superoxide anion and IL-1β production in VSMCs of SHR but had no impact on exogenous Ang II-induced VSMC migration and on superoxide anion and IL-1β production in WKY rats and SHR. These results indicate that miR155-5p inhibits VSMC migration in SHR by suppressing ACE expression and its downstream production of Ang II, superoxide anion, and inflammatory factors. However, miR155-5p had no effects on exogenous Ang II-induced VSMC migration.